Epidemiology of Adult Open Globe Injury. Issue 7 (October 2016) - Batur, Muhammed; Seven, Erbil; Esmer, Oktay; Akaltun, Mahmut Nedim; Yasar, Tekin; Cinal, Adnan
Abstract : Objective: The aim of this study was to evaluate the epidemiology and outcomes of adult open globe injuries (OGI) in the eastern part of Turkey. Methods: The retrospective study included all the patients who were diagnosed with OGI (436 eyes in 425 patients) at our clinic between 1997 and 2015. The OGI patients aged over 16 years were included into the study. Open globe injuries were classified according to the Ocular Trauma Classification. Age, gender, medical history, time between trauma and hospital admission, and mechanism of injury were recorded for each patient. Results: The incidence of OGI in adults was found to be 3.40/100, 000, with 5.00/100, 000 in males and 1.67/100, 000 in females. Open globe injuries were mostly seen in the age group of 17 to 29 years and in October and November. The patients included 79.5% males and 20.5% females. Intraocular foreign body was detected in 99 (22.7%) eyes. A strong, linear, negative correlation was found between the Ocular Trauma Classification values and final visual LogMAR ( r p = −0.602, P = 0.0001). The most common mechanism of injury was occupational accident (38.4%). Conclusion: Open globe injuries remain a serious public health problem, resulting in significant vision loss. Open globe injuries are mostly seen in the young, middle-aged, and male working population. Additional preventive measures should be taken for the individuals in these groups.